FREQUENCY OF CLAR AND JAK2 MUTATIONS IN SUDANESE CHRONIC MYELOID LEUKEMIA PATIENTS WITH PHILADELPHIA-POSITIVE DISEASE - Yasin, Elrashed B; Yasin, Aymen (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: It is well-established that myeloproliferative diseases coexist with CLAR and JAK2. In Ph+ chronic myeloid leukemia (CML), only a few case reports indicate the existence of CLAR, JAK2V617F, and JAK2 exon 12 mutations. Methods: This study examined CALR and JAK2 mutation profiles in Sudanese Chronic Myeloid Leukemia patients with Philadelphia-positive patients. Blood samples were collected from 100 patients with Ph+ CML chromosomes. Results for the JAK2V617F mutation were confirmed using the TaqMan® Mutation Detection Assay, and the four common mutations on exon 12 and CLAR mutations were confirmed using allele-specific PCR (AS-PCR) and Sanger sequencing. Results: CML patients with CALR frameshift mutations were detected in two patients (2%), patients with JAK2 exon 12 mutations were found in two patients (2%), and patients with JAK2V617F mutations made up 4 (4%) of the total CML patients. No significant relationships existed between mutations and age, WBC, RBC, Hb, HCT, or platelet parameters. Patients with CLAR, JAK2 exon 12, and JAK2V617F mutations have normal leukocyte counts and lower values compared to triple-negative Ph+ CML, but these differences are not statistically significant (p values for each 0.084, 0.173, and 0.072). Conclusion: It is conceivable for Ph+ CML and all mutations to coexist.